Novel Missense ALDH3A2 Mutation in a Patient with Sjögren–Larsson Syndrome - Tagiyev, Anar; Cavdarli, Busranur; Konuskan, Bahadir; Topaloglu, Haluk (Journal of Pediatric Neurology, 2020)
An 11-year-old boy presented with toe-walking, hyperkeratosis of the skin, dysarthric speech, and mild mental retardation. On neurological examination, mild fasciculation in the eyelids and bilateral end-point nystagmus were noted. Speech quality was dysarthric, muscle tone, strength, and deep tendon reflexes increased tone, reflexes, and mild weakness (4/5), and bilateral Babinski sign was noted in the lower extremities. Cranial magnetic resonance imaging revealed a T2-signal increase in the right temporal lobe. Sjögren–Larsson syndrome based on clinical and neurological findings was confirmed with the identification of a homozygous c.983T˃C(p.Met328Thr) mutation in the ALDH3A2 gene; both parents were heterozygous for the same mutation.
Keywords: congenital ichthyosis; mental retardation; enzyme deficient